2021
DOI: 10.3390/jcm10112449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermittent Theta Burst Stimulation on the Neural Processing of Emotional Stimuli in Healthy Volunteers

Abstract: Background: Intermittent theta burst stimulation (iTBS) is a form of repetitive transcranial magnetic stimulation that has shown to be effective in treatment-resistant depression. Through studying the effect of iTBS on healthy subjects, we wished to attain a greater understanding of its impact on the brain. Our objective was to assess whether 10 iTBS sessions altered the neural processing of emotional stimuli, mood and brain anatomy in healthy subjects. Methods: In this double-blind randomized sham-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Although it is highly questionable if the studies can be compared because of the use of different mood rating constructs and rTMS protocols, the finding that left prefrontal rTMS results in a significant reduction in the BDI indicates a contrary effect compared to the lateralized effect of the former studies. While 2 other studies found at least partial effects of prefrontal rTMS on mood in healthy subjects [ 11 , 12 ] and another study demonstrated that one intermittent Theta Burst Stimulation (iTBS) session can increase positive affective processing in healthy individuals [ 13 ], 11 other studies failed to demonstrate any mood effects in healthy subjects following prefrontal rTMS [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], iTBS or cTBS [ 25 , 26 , 27 ] even after 10 iTBS sessions [ 27 ]. In summary, the data on mood changes in healthy participants after rTMS is inconsistent for both older protocols (HF rTMS or LF rTMS) as well as for TBS (cTBS or iTBS), with the number of studies yielding negative results being predominant.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is highly questionable if the studies can be compared because of the use of different mood rating constructs and rTMS protocols, the finding that left prefrontal rTMS results in a significant reduction in the BDI indicates a contrary effect compared to the lateralized effect of the former studies. While 2 other studies found at least partial effects of prefrontal rTMS on mood in healthy subjects [ 11 , 12 ] and another study demonstrated that one intermittent Theta Burst Stimulation (iTBS) session can increase positive affective processing in healthy individuals [ 13 ], 11 other studies failed to demonstrate any mood effects in healthy subjects following prefrontal rTMS [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], iTBS or cTBS [ 25 , 26 , 27 ] even after 10 iTBS sessions [ 27 ]. In summary, the data on mood changes in healthy participants after rTMS is inconsistent for both older protocols (HF rTMS or LF rTMS) as well as for TBS (cTBS or iTBS), with the number of studies yielding negative results being predominant.…”
Section: Introductionmentioning
confidence: 99%
“…16 Moreover, iTBS over the left DLPFC increases positive affective processing for word recall 17 and neural activity in the left anterior insula when presented with negative stimuli. 18 However, most studies investigated the effects of only a single or two iTBS sessions on mood and/or emotion processing in healthy volunteers, with only one including clinical participants taking antidepressant medications. 14 To our knowledge, there has been no study on the effect of multiple sessions of biTBS monotherapy on emotional processing in patients with MDD.…”
mentioning
confidence: 99%
“…For example, HF rTMS on the left DLPFC decreases a healthy individual's attentional engagement with angry faces 15,16 and improves the processing of positive stimuli 16 . Moreover, iTBS over the left DLPFC increases positive affective processing for word recall 17 and neural activity in the left anterior insula when presented with negative stimuli 18 . However, most studies investigated the effects of only a single or two iTBS sessions on mood and/or emotion processing in healthy volunteers, with only one including clinical participants taking antidepressant medications 14 .…”
mentioning
confidence: 99%